Surface location of a Bacteroides gingivalis glycylprolyl protease. - Grenier, D (1989)
Various immunological methods were used to localize a glycylprolyl protease previously isolated from Bacteroides gingivalis ATCC 33277. The results obtained by enzyme-linked immunosorbent assay, indirect immunofluorescence staining, and indirect immunogold labeling suggest that the glycylprolyl protease is present on the surface of the cell outer membrane and is specific to B. gingivalis strains. The enzyme was removed from the cell envelope by treatment of the whole cells with sodium dodecyl sulfate, Triton X-100, sodium deoxycholate, and proteinase K.